Post-viral alterations in periodontal health in individuals recovering from COVID-19 - Roganović, Jelena; Barać, Milena; Miličić, Biljana; Petrović, Milan; Sredojević, Stefan; Krasavčević, Ana Đinić; Nikolić-Jakoba, Nataša (Frontiers in Oral Health, 2025)
This study explores post-viral immune modulation in periodontal health using COVID-19 convalescence as a model. We hypothesized that post-COVID-19 recovery induces epigenetic alterations, measurable through salivary methyl-transferase-like 3 (METTL3) expression and clinical-periodontal parameters. The present research comprises results from two studies: the clinical study, which included a total of 83 systemically healthy adults stratified into four groups according to periodontal status and COVID-19 history, and the laboratory study on human parotid gland samples (n = 10). Full-mouth periodontal status and unstimulated morning saliva were obtained. Glandular METTL3 and fat mass and obesity-associated factor as well as salivary METTL3 and cortisol were quantified using ELISA; psychological stress was assessed with the Perceived Stress Scale −10. Effect sizes were assessed using ANOVA and multivariable linear regression, and receiver operating characteristic (ROC) curves were generated for METTL3. Decreased levels of METTL3 in parotid tissue and in saliva of COVID-19 convalescents were found. Prior COVID-19 was significantly associated with METTL3 and plaque index (PI) as predictors, when adjusted for age, gender, periodontitis, and salivary cortisol. Strong associations between METTL3 and PI were found. Stress scores and cortisol did not differ between groups. Thus, downregulation of salivary METTL3 and concomitant plaque index reduction characterize the late convalescent phase of COVID-19. These epigenetic changes may reflect post-viral changes in parotid gland and periodontal health homeostasis and warrant longitudinal research confirmation.